2015
DOI: 10.1111/pai.12432
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to make a diagnosis of raw, heated, and baked egg allergy in children using cutoffs? A systematic review

Abstract: The diagnosis of IgE-mediated egg allergy lies both on a compatible clinical history and on the results of skin prick tests (SPTs) and IgEs levels. Both tests have good sensitivity but low specificity. For this reason, oral food challenge (OFC) is the ultimate gold standard for the diagnosis. The aim of this study was to systematically review the literature in order to identify, analyze, and synthesize the predictive value of SPT and specific IgEs both to egg white and to main egg allergens and to review the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 64 publications
(224 reference statements)
2
43
0
Order By: Relevance
“…On the other hand, patch tests in FA do not have a diagnostic value, particularly with egg and cow's milk . Although numerous attempts have been made to determine the diagnostic cutoff of specific IgE and SPT for egg allergy, no cutoff value by itself may allow a firm diagnosis of raw, heated, or baked egg allergy . Children with IgE‐mediated hen's egg allergy often tolerate baked egg within a wheat matrix .…”
Section: Natural Historymentioning
confidence: 99%
“…On the other hand, patch tests in FA do not have a diagnostic value, particularly with egg and cow's milk . Although numerous attempts have been made to determine the diagnostic cutoff of specific IgE and SPT for egg allergy, no cutoff value by itself may allow a firm diagnosis of raw, heated, or baked egg allergy . Children with IgE‐mediated hen's egg allergy often tolerate baked egg within a wheat matrix .…”
Section: Natural Historymentioning
confidence: 99%
“…Baked egg‐reactive subjects have larger skin prick test (SPT) wheals and greater EW‐, OVA‐ and OVM‐specific IgE levels than baked egg‐tolerant subjects but with a great deal of overlap . Cutoffs of specific IgE and SPT for diagnosing baked egg allergy are still lacking . All these markers rely on a level of response to a fraction or antigen.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, which was conducted using children <2 years of age, allergy to raw egg seems very likely when, using EW extract, SPT generates urticaria ≥4 mm, or when sIgEs are ≥1.7 kU A /L. In children ≥2 years, OFC could be avoided when SPT wheals with EW extract are ≥10 mm, prick by prick wheals are ≥14 mm, or specific IgE is ≥7.3 kU A /L 28. Compared with these reported values, cutoffs found in our study were rather high: for ImmunoCAP, EW‐sIgEs ≥18.7 kU A /L and OM‐sIgEs ≥5.7 kU A /L were predictive of egg allergy in children <2 years, while in children ≥2 years, EW‐sIgEs ≥11.5 kU A /L and OM‐sIgEs ≥6.1 kU A /L were predictive (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a systematic review reported on the diagnostic accuracy of skin prick testing (SPT) vs sIgE in the clinical diagnosis of food allergy 28. The authors comprehensively reviewed the risk of bias in the literature and proposed cutoff values at which SPT and sIgE measured by ImmunoCAP were diagnostic for EW allergy.…”
Section: Discussionmentioning
confidence: 99%